Elastic-plastic failure analysis on interacting cracks with aerospace engineering applications - Zhang, Chang Hua (2014)
This Project is aiming to understand of the basic engineering mechanic concept in aerospace material structure, and learn the basic theory of elastic-plastic fracture mechanics. By using the finite element analysis method, to perform the stress study for various interacting crack, and calculate the stress intensity factor and plastic zone size for interacting cracks in solids.